Prevalence and Intensity of Catfish Parasites (clarias sp.) "Mino Ngremboko” Group Cultivation Pool, Grabag Village, Grabag District, Purworejo Regency - Ayuningtyas Ayuningtyas; Muhammad Tri Aji; Abdul Qadir Jailani; Eric Armando (Journal of Aquaculture Science, 2021)
Parasite infections in aquaculture can trigger primary infections due to decreased fish immunity making it easier for other microorganisms, both bacteria and viruses, to enter the fish's body. This study aims to identify, calculate the prevalence and intensity of parasites that found in catfish ponds of the "Mino Ngremboko" fish farmers group in Grabag Village, Grabag District, Purworejo Regency. This study used the scraping method by reviewing the gills, mucus from the skin, fins and digestive tract onto a glass object which was then observed microscopically using a light microscope with a magnification of 10-40x. The parasites found were ectoparasites consisting of 6 species; Trichodina sp., Tetrahymena sp., Gyrodactylus sp., Epistylis sp., and Dactylogyrus sp. No parasites were found from the endoparasite and hematozoa groups. The highest prevalence was Dactylogyrus sp. with a prevalence rate of 54% and the lowest was Dinoflagella with a prevalence rate of 10%. The highest and lowest parasite intensities were Epistylis sp. (18,0 ind./infected fish) and Dactylogyrus sp. (2,8 ind./infected fish), respectively. It can be concluded that the level of parasitic infections in the fish farmer groups ponds was at the "common-usually” level based on William and Bunkley's prevalence criteria.Key words: Clarias sp., identification of Parasite, prevalence, intensity, Mino Ngremboko